The Prevalence and Risk Factors of Stress Urinary Incontinence in Postpartum - Pratiwi, Renny; Suparman, Eddy; Lengkong, Rudy A (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To know the incidence of stress urinary incontinence in postpartum and determine the relationship among age, parity, infant birth weight, mode of delivery, episiotomy and perineum rupture. Method: This study used cross sectional analytic design. Qualified subjects from inclusion criteria were interviewed by researchers using pre-defined MESA questioner. Subjects with stress urinary incontinence were found from the questionnaire result. The acquired data was measured and analyzed using SPSS v. 22.0 software and discussed using available literature. Result: From 162 subjects, 36 cases (22.22%) had stress urinary incontinence, 47.22% aging ? 35 years old, 72.22% had multiple pregnancies, 88.89% had per vaginal delivery. Using multivariate logistic regression test, we found there was a relationship between stress urinary incontinence with age and parity (p 35 years old and multiple parities. Keywords: multiple parities, post-partum, stress urinary incontinence